Measurement and evaluation of indoor air quality in naturally ventilated residential buildings. Issue 10 (December 2019) - Yin, Haiguo; Liu, Chunxue; Zhang, Leiming; Li, Angui; Ma, Zhenjun
This paper presents the field measurement and evaluation of the indoor air quality of 25 naturally ventilated residential buildings in northwestern China. Concentrations of formaldehyde, benzene, toluene, total volatile organic compounds, nitrogen dioxide and PM2.5, and air infiltration rate were measured in the bedroom, living room and kitchen of each building in different seasons. The results show that the concentration of formaldehyde can be used as a representative index of indoor gaseous pollutants, and that formaldehyde concentrations in various locations measured were highest in spring and lowest in autumn. PM2.5 concentration was the most important influencing factor of indoor air quality in winter, and concentration of outdoor PM2.5 was the key factor under hazy weather conditions. The median air infiltration rate was around 0.35 h −1 in bedrooms and 0.8 h −1 in kitchens, and these should be increased to 0.66 h −1 and 1.6 h −1, respectively, to provide acceptable indoor air quality in northwestern China. The findings obtained from this study can be used to understand where and how to improve the indoor air quality of naturally ventilated buildings in northwestern China. The data can also contribute to the development of a national database for improving residential ventilation, energy efficiency and indoor air quality.